Dark Triad Personality and Cyber-Aggression: A Study of Second Social Media Account Users - Asri, Herini Wahyu; Hendriyani, Rulita (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The growing use of social media in Indonesia has led to the emergence of the second account phenomenon-alternative accounts used in a more private and anonymous manner. These accounts are often utilized as spaces for self-expression beyond social expectations but can also serve as platforms for deviant behaviors such as cyber-aggression. This study aims to examine the relationship between Dark Triad personality traits-comprising Machiavellianism, Psychopathy, and Narcissism-and cyber-aggression among second account users on social media. A quantitative correlational approach was employed, involving 475 participants who own second accounts. Instruments used include the Cyber-Aggression Questionnaire for Adolescents (CYBA) and the Indonesian version of the Dark Triad Dirty Dozen (DTDD). Multiple linear regression analysis revealed that Machiavellianism (β = 0.2231, p < .001) and Psychopathy (β = 0.2727, p < .001) significantly influenced cyber-aggression, while Narcissism did not show a significant effect (β = 0.0690, p = 0.179). The model explained 20% of the variance in cyber-aggression behavior (Adjusted R² = 0.200). These findings indicate that individuals with Machiavellian and subclinical psychopathic traits are more prone to engaging in online aggression, particularly in contexts that offer anonymity. This study underscores the importance of considering personality aspects in understanding deviant behavior on social media and highlights the need for psychological interventions in anonymous digital spaces.Penggunaan media sosial yang semakin meluas di Indonesia mendorong munculnya fenomena penggunaan second account, yaitu akun alternatif yang digunakan secara lebih privat dan anonim. Akun ini kerap dimanfaatkan sebagai ruang ekspresi diri di luar ekspektasi sosial, namun juga dapat menjadi sarana untuk mengekspresikan perilaku menyimpang seperti cyber-aggression. Penelitian ini bertujuan untuk mengkaji hubungan antara kepribadian Dark Triad yang terdiri dari Machiavellianism, Psychopathy, dan Narcissism dengan perilaku cyber-aggression pada pengguna second account media sosial. Pendekatan kuantitatif korelasional digunakan dengan melibatkan 475 partisipan yang memiliki second account. Instrumen yang digunakan adalah Cyber-Aggression Questionnaire for Adolescents (CYBA) dan Dark Triad Dirty Dozen (DTDD) versi Indonesia. Hasil analisis regresi linear berganda menunjukkan bahwa Machiavellianism (β = 0.2231, p < .001) dan Psychopathy (β = 0.2727, p < .001) berpengaruh signifikan terhadap cyber-aggression, sedangkan Narcissism tidak menunjukkan pengaruh yang signifikan (β = 0.0690, p = 0.179). Model menjelaskan 20% variansi perilaku cyber-aggression (Adjusted R² = 0.200). Temuan ini mengindikasikan bahwa individu dengan sifat Machiavellian dan psikopat subklinis lebih rentan melakukan agresi daring, terutama dalam konteks akun yang memberikan anonimitas. Penelitian ini menyoroti pentingnya perhatian terhadap aspek kepribadian dalam memahami perilaku menyimpang di media sosial serta perlunya intervensi psikologis dalam ruang digital yang bersifat anonim.